Determination of Capacities of Two-Circuit Open-Air Electric Power Lines with Voltage of 35 kV - M. A. Korotkevich; A. J. Ohremenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Calculations of phase capacity of two-circuit open-air electric power lines with voltage of 35 kV relative to the ground have been carried out. The paper gives values of capacities of open-air electric power lines with voltage of 35 kV which are located on two-circuit supports depending on the operational mode of the second circuit. The values of capacity of a two- circuit electric power line have been determined provided that circuits of various rated voltage are located on a line. Changes in capacity of an electric power line with voltage of 35 kV have been calculated in comparison with the capacity of an one-circuit line depending on a distance between axes and the operational mode of the second line, if the lines are parallel.